Task Coordination in an Agile Distributed Software Development Environment - Mak, D.K.M.; Kruchten, P.B. (2006 Canadian Conference on Electrical and Computer Engineering, 2006)
As both distributed software development (DSD) and agile development practices become more popular, the problem of task coordination in an agile DSD environment becomes more pertinent. Even though task allocation has been a subject of study for many years, the team dynamics in an agile DSD environment makes the nature of task coordination distinctly different from that in other disciplines. This paper proposes a solution to the problem of remote task allocation and coordination in an agile DSD environment. It combines current practices in software project management, such as object-oriented process modeling and critical-path analysis, and methodologies from other fields, such as workflow management and management science. It also describes NextMove, a Java/Eclipse-based distributed tool that would assist project managers in making day-to-day task allocation decisions, increasing transparency throughout the project, as well as complementing other modes of communication in a DSD environment